A topographic anatomical study of the equine epiploic foramen and comparison with laparoscopic visualisation. (25th June 2014) - van Bergen, T.; Doom, M.; van den Broeck, W.; Wiemer, P.; Clegg, P. D.; Cornillie, P.; Martens, A.
Summary: Reasons for performing study: There are no previous studies correlating the anatomy of the equine epiploic foramen and its defining structures with laparoscopic images. Objectives: The purpose of this study was to describe the precise anatomy of the epiploic foramen and omental vestibule, to quantify the dimensions of the epiploic foramen and to relate these findings to laparoscopic images. Study design: Descriptive study of cadaver material and laparoscopic images. Methods: Thirty‐two horses subjected to euthanasia for reasons unrelated to colic were studied. Two cadavers were used to make vascular casts of the coeliac artery and portal vein. In 30 cadavers the epiploic foramen and omental vestibule were cast with a polyurethane prepolymer immediately after euthanasia. The cast served as a landmark during dissection and the circumference of the epiploic foramen was measured from these casts. Histology was performed on structures defining the epiploic foramen in 2 horses. Laparoscopic images from 6 standing right flank procedures were reviewed. Results: The defining structures of the epiploic foramen and omental vestibule are the hepatoduodenal ligament, hepatogastric ligament and the gastropancreatic and hepatopancreatic folds. The hepatoduodenal ligament has a secondary fold which forms the ventral border of the epiploic foramen, consisting of a central connective tissue core of mainly elastin fibres. The hepatic artery for part of its course is incorporated in the hepatoduodenal ligament. All these structures are clearly visible laparoscopically. The mean circumference of the epiploic foramen is 11.6 ± 2.6 cm and its circumference is positively correlated with body weight but is unrelated to age or gender. Conclusions: Several clinically relevant structures delineate the epiploic foramen. Its defining structure consists, in part, of elastin fibres. Anatomical and laparoscopic knowledge may assist surgeons in developing interventions to treat diseases involving the epiploic foramen.